The meanings of death and dying: the perspective of crack users (Revista Latino-Americana de Enfermagem, 2012)
The consumption of crack can constitute in an inauthentic form of the existence that leads a person to live improperly the being-toward-death. Given this reality, this study aimed to comprehend the significance of death and dying for the user of crack and to unveil the meanings attributed to this significance. This qualitative study was conducted, based on the phenomenological method, with 12 crack users, in the therapeutic process, in a Psychosocial Care Center - Alcohol and Drugs (CAPSad), in the period from February to April 2011, in Teresina, Piauí. The results show that death is signified, ontically, as a companion, a partner, a passage, a journey and as the crack itself. It was concluded that this significance expressed an inauthentic experience, directed toward the incessant interaction with crack, accompanied by a feeling of nullity and relational disengagement.